The Effect of Shape Variations of Weirs and Stilling Basin Type USBR-I on the Length of the Hydraulic Jump and Energy Loss - Abdurrosyid , Jaji; Purwanto , Edi; Renaningsih (Theory and Applications of Engineering Research Vol. 2, 2024)
The purpose of this study was to determine the effect of shape variations of weirs and stilling basin type USBR-I on the length of the hydraulic jump and energy loss.The Crest of weir is an important part of dam construction because the function is releasing water from the upstream part of the dam. The effect of a dam can create supercritical flow (supercritical) downstream of the weir and cause a water jump (hydraulic jump) which if left untreated will occur local scour the downstream. weir. In weir planning, it is necessary to take into the dam will be used because it affects the flow conditions downstream of the weir. This study employed primary data from laboratory testing using a Recirculating Flume instrument of 10.0 m long, 0.30 m wide channel, and 0.60 m flume height This was conducted by making variations in the form of test objects, namely ogee crest weirs, 1 radius round type weirs, and 2 radius round type weirs using the USBR-I stilling basin type which was then tested in the laboratory using five different variations of flow rates, namely 3000 cm3/s, 3500 cm3/s, 4000 cm3/s, 4500 cm3/s, and 5000 cm3/s. To determine the most effective way to shorten the hydraulic jump's length and reduce its energy, the data test was analyzed by using equations/formulas and graphically potrayed to produce research findings and compared with crest variations. The results in the study show the effect of dam crest variations on the length of the hydraulic jump (Lj) based on the maximum discharge, which is round type 1 radius of dam crest with 125 cm longest Lj, then a 2 radius round type with the longest Lj 136 cm, and an ogee type with the longest Lj. 142 cm. For the effect of variations of dam crest on energy loss (hf), the average value of the five running discharge experiments on each specimen was taken, the variation of the dam crest that had the greatest to the smallest energy loss (hf) value was the 2 radius round type dam with hf average 31,429 cm, ogee type dam with an average hf of 31.404 cm, and round type 1 radius dam with an average hf of 30.456 cm. Finally, it was concluded that the variation of the dam crest is the most efficient in reducing energy is the 2 radius round type dam crest.